DAMPAK KECANDUAN PERMAINAN PLAYSTATION (PS) DIKALANGAN MAHASISWA UNIVERSITAS RIAU “(Studi Kasus Mahasiswa yang Bermain di Rental Playstation(Ps) Farel GameStation di Jalan Manyar Sakti)“ - Azwar Efendi; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The game is one of the activities undertaken by someone who makes her feel happy and feel comforted by it. Types of games that are popular in the modern era such as PSP, Playstation (Ps), online games and so forth. From the variety of games that appear this modern era of the PlayStation (PS) is the most popular by all people, both children, teens, and even adults. Issues discussed in this study How playstation player characteristics (Ps), what is the motivation of students at the University of Riau to play playstation games (Ps) and how it impacts the playstation game addiction (Ps) among University Students Riau. The goal is to identify the characteristics of the player playstation (Ps), to determine the motivation of Riau University students to play playstation games (Ps) and to determine and describe the impact playstation game addiction (Ps) among students at the University of Riau. The population in this study is still active Riau University students who came to college to play playstation (Ps) in Farel game station by 30 respondents. The data obtained in this study will use descriptive quantitative method. The research instruments used were questionnaires, interviews, participant observation and documentation. The technique used in determining the sample is accidental sampling method that is based on accidental sampling technique, which is met with a researcher who happened to be sampled are considered suitable or collectively, the sampling method by way of choosing who happened to be there or encountered. The theory used for this problem is that the theory of Max Weber Theory of Social Action. Results of research conducted in general it can be said that the author playstation (Ps) has an impact on the economy, pendidikaan, health, social and religious impact.Keywords: Playstation (Ps), Impact of Addiction, Riau University Students